KRaiRobotic SCILAB Toolbox - Udompuchphon, S.; Yanyong, S.; Kaitwanidvilai, S. (My University, 2023)
This paper presents a developed toolbox in SCILAB that is useful for teaching and training purposes in the field of robotics. The essential commands in kinematics have been developed to simulate a robotic arm, and the paper demonstrates the modeling of a specified robot arm, PUMA560, by comparing the results with those obtained using MATLAB software. The conclusion discusses the next steps for future work.
Keywords: Kinematics; Robotics Toolbox; SCILAB; Simulation